Jacobian-Based Task-Space Motion Planning for MRI-Actuated Continuum Robots - Greigarn, Tipakorn (IEEE Robot Autom Lett, 2018)
Robot-assisted medical interventions, such as robotic catheter ablation, often require the robot to perform tasks on a tissue surface. This paper presents a task-space motion planning method that generates actuation trajectories which steer the end- effector of the MRI-actuated robot along desired trajectories on the surface. The continuum robot is modeled using the pseudo-rigid-body model, where the continuum body of the robot is approximated by rigid links joined by flexible joints. The quasistatic motion model of the robot is formulated as a potential energy minimization problem. The Jacobian of the quasistatic motion model is used in calculating the actuations that steer the tip in the desired directions. The proposed method is validated experimentally in a clinical 3-T MRI scanner.